Demonising the Other : The Criminalisation of Morality - Whitehead, Philip, 1952- (Book collections on Project MUSE., 2018)
Throughout history there has always been an 'other', often based on culture, race, gender or class, that has been demonised by the majority. Whitehead challenges the idea that this is an inevitable fact of life. This important book offers a resolution that benefits society as a whole rather than just the powerful few.